How To Enhance Firm Value In The Jakarta Islamic Index (Jii) Through Profitability, Csr And Gcg - Pasaribu, Nona Soraya; Rasyid, Arbanur; Rukiah, Rukiah; Muzamil, Sanupal; Nasirin, Wanda Khairun; Pane, Mujahidun Hapisni (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
The company's profitability will reflect the company's financial performance. Good financial performance can increase the value of the company, which will be reflected in the market price of its shares and increase the prosperity of shareholders (stakeholders). Profitability is also a factor that makes management free and flexible in disclosing corporate social responsibility to shareholders. Thus, the higher the level of company profitability, the greater the disclosure of information. So, this study intends to see how profitability affects firm value and whether corporate social responsibility and good corporate governance effectively moderate profitability's effect on manufacturing companies’ value in the Jakarta Islamic Index (JII). Therefore, this study is important and serves as material for investors and potential investors to consider and reference in selecting companies. Various theories support this study, as the grand theory is the agency theory and the signaling theory. The middle theory of this research is contract theory, and the applied theory is firm value theory. This theory is to measure the company's selling value or growth value for shareholders, the company's value, which will be reflected in the market price of its shares. This research was conducted using a quantitative method, which will be carried out in 2021 at a manufacturing company registered on the Jakarta Islamic Index (JII). The sampling technique used was purposive sampling, with twenty-four companies listed on the Jakarta Islamic Index (JII). Considering that the model in this study is a causality model for several manufacturing companies, to test the hypothesis, cross-sectional data is used with the structural equation modeling (SEM) approach using the partial least squares program (PLS 4.0). The results of the profitability direct effect test do not directly affect firm value; the direct effect test results of CSR moderation do not directly affect firm value; and so do the GCG direct effect test results, which do not affect firm value.